الصفة المشبهة فى القرآن الكريم: دراسة نحوية صرفية دلالية - اليمنى، جويرية محمد; النور، فضل الله (جامعة السودان للعلوم والتكنولوجيا - معهد العلوم والبحوث الإسلامية, 2016)
The Likened Adjectives are one of the derivatives which act as a noun in concordance to the functional measurements of the Participial Subject, but it indicates in most of its form to the constancy. However, the Participial Subject has unstable denotation which swings between renewability and stability where the Likened Adjective is used for the past that is connected to the continuous present, on the other hand, the participial subject is used for the three times. This paper studies the Likened Adjective grammatically, morphologically and semantically, however, it includes morphological investigation for structures of the Likened Adjectives by using example for each structure. Also, it studies the function of the Likened Adjective through analyzing correspondence in the Likened Adjectives and comparing its function to that of the participial noun as well as showing similarities and differences between them. Moreover, this study discusses meaning of the various structures of Likened Adjectives with the help of clarifying examples besides providing scholars' point of view about them This study used analytical and descriptive methods. This study shows that the structures of the Likened Adjectives are numerous and multiple, and have different meanings which may overlap.
الصفة المشبهة إحدى المشتقات التي تعمل عمل الفعل وفق ضوابط عمل اسم الفاعل إلا أنها تدل في معظم حالاتها على الثبوت، أما اسم الفاعل فله دلالة متأرجحة ما بين التجدد والثبوت وتكون الصفة المشبهة للماضي المتصل بالزمن الحاضر الدائم، أما اسم الفاعل فيكون للأزمنة الثلاثة. ومن خلال هذه الورقة نتناول الصفة المشبهة في دراسة نحوية، صرفية، ودلالية وقد تضمنت هذه الدراسة، دراسة أبنية الصفة المشبهة دراسة صرفية مع التمثيل لها، كما قاولت إعمال الصفة المشبهة وذلك من خلال دراسة المطابقة في الصفة المشبهة ومقارنة إعمالها بإعمال اسم الفاعل وتوضيح نقاط التشابه والاختلاف بينهما. اتبعت الدراسة المنهج التحليلي الوصفي، كما تعرضت هذه الدراسة أيضا لدلالة أبنية الصفة المشبهة المختلفة مع التمثيل لها وذكر أراء العلماء فيها. وقد رأينا من خلال هذه الدراسة أن أبنية الصفة المشبهة كثيرة ومتعددة وأن لها دلالات مختلفة وقد تتداخل هذه الدلالات فيما بينها.
Keywords: النحو العربى -- المشتقات -- الصفة المشبهة -- اسم الفاعل -- الدلالات